A conceitualização sobre estruturas aditivas e multiplicativas no uso de formas de representação visual em uma interface educativa - Queiroz, Ana Emilia de Melo (2012)
The software Gérard locatedat http://www.univasf.edu.br/~ana.queiroz/GerardApplet.html is an educational interface dedicated to the training of teachers about Additive and Multiplicative Structures, which are more popularly known as addition, subtraction, multiplication and division. Preliminary work of the author stated the effectiveness of this interface in the learning of specific concepts. However, the conceptualization or process through which such learning occurred was not analyzed. This process includes the mathematical concepts and its metaphorical representations; the user and his previous knowledge, as well as the interaction modalities on the computer. The aim of this study was, therefore, to identify the conceptualization of additive and multiplicative structures in the use of Gérard interfaces. This is an exploratory quasi-experimental qualitative study carried out with (07) seven teachers in two schools in the city of Juazeiro/ BA. Data collection occurred through filming, recordings and semi-structured interviews. The obtained results indicate a change in the discourse of the users, not of the status of the concept, but of elements relative to the reflexive, co-existent process during the realization of the task. Furthermore, there still was a predominance of terms related to affective and motivational factors, as well as meta conceptual consciousness, which refers to the learner's thinking about the relationship between their previous knowledge and the cognitive demands of the task. Such results can be used as a input for the construction of educational interfaces aiming to teach additive and multiplicative structures.